PODCASTING THROUGH THE PANDEMIC: STUDENTS’ PERCEPTIONS AND PERFORMANCE AT AN ODL INSTITUTION - Kershnee Sevnarayan (EDUTECH, 2022)
Abstract: The pandemic has prompted the use of supplemental learning tools such as podcasts to become increasingly used to bridge the gap between lecturers and students. This paper argues that podcasting not only sharpens students’ listening skills but also enables them to engage with content more efficiently. This paper is underpinned by the transactional distance theory and the community of inquiry theory to understand the role of podcasting in teaching and learning in distance education. In an attempt to decrease transactional distance, this case study evaluates students’ perceptions of the implementation of podcasts in one South African ODL university, as an example, and investigates the effectiveness of using podcasts as a supplemental teaching tool in an English language module. The findings suggest that supplemental learning does decrease the transactional distance between lecturers-students and students-content. Moreover, the study found that podcasts tend to foster a teaching, social and cognitive presence that forms a community of inquiry. This paper concludes by providing pedagogical recommendations for teacher and student development in distance education contexts.